THE USE OF FRACTAL GEOMETRY ELEMENTS AS A MEANS OF AESTHETIC EDUCATION OF PRIMARY SCHOOL STUDENTS - Sergeeva, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Currently, the issue of aesthetic education is becoming one of the key issues in the field of education. The relevance of the article is due to the fact that mathematics has great aesthetic potential, which is not always revealed in the process of teaching mathematics in elementary school. An important role in revealing the beauty of mathematical content in elementary school is played by the familiarity of schoolchildren with a young rapidly developing mathematical field - fractal geometry. In order to prove the effectiveness of using fractal geometry elements for the formation of aesthetic representations of younger schoolchildren, a formative experiment was carried out, with the help of testing we diagnosed changes in the level of formed aesthetic representations, feelings and judgments of younger schoolchildren during the experimental work. The tools and methods of using the elements of fractal geometry in the study of mathematics in elementary school are described. The results of the study allow us to conclude that the familiarity of primary schoolchildren with fractals increases the interest of students in mathematics. The amazing simplicity of fractals and the diversity of their forms contributes to the formation of aesthetic ideas and feelings among younger students. The construction of fractals in the study of geometric objects in elementary school makes it possible to show students that aesthetic pleasure is provided not only by art, but also by the joy of creativity in other fields of activity, including teaching.